Upper midline correction in conjunction with rapid maxillary expansion - (:unkn) unknown (MOSBY, INC, 2006)
Introduction: The purpose of this study was to investigate a simple method for correcting upper dental midline shift, by physiologic movement of the incisors during the retention period of rapid maxillary expansion. Methods: Thirty-two patients with upper midline shifts due to constricted maxillae and anterior crowding were selected. All had undergone radiological and clinical examinations to be sure that the midline shift was not functional and was caused only by crowding. The patients were randomly divided into 2 groups. In both groups, acrylic cap splint type expansion appliances were used. In group 1, the acrylic cap covered all the dentition except the incisors and the canine on the shifted side. After expansion, the incisors on the shifted side were allowed to move toward the midline, and the incisors of the other side were held by the acrylic cap. In group 2, the acrylic cap covered only the posterior teeth, from the first premolars on both sides. After expansion, the incisors on the shifted side were allowed to move toward the midline diastema, whereas those on the other side were held in place by ligation of the brackets, which had been placed immediately after expansion. Results: In both groups, the midline shift was corrected by the movement of the shifted incisors toward the midline diastema, without orthodontic force. Conclusions: Residual or unwanted forces produced during rapid maxillary expansion can be used to correct an upper dental midline shift.
Keywords: MIDPALATAL SUTURE